The Role Of Pharmacists In Managing Chronic Diseases (Journal of Namibian Studies : History Politics Culture, 2024)
This essay describes several important roles for pharmacists in improving outcomes in managing chronic diseases. As medication management is the foundation of treating people with chronic diseases, pharmacists play important roles in reviewing patient therapeutic plans, collaborating with prescribers, and working with patients. A number of countries around the world are recognizing the need for better managed chronic diseases and the corresponding role of pharmacists to practice to the full extent of their education. These evolving roles increasingly recognize the impact on patient outcomes that trained pharmacists can have when effectively working as part of the team.The essay describes how these and other roles for pharmacists evolved, while also noting some of the tensions in the move towards collaborative care models. Despite the tensions, however, patient outcome data is evident for the effectiveness of care in these models when pharmacists practice them to full scope. The global trend to empower and well-position pharmacists to provide care for patients with chronic conditions will likely grow as these care and economic data are more widely disseminated and as access to qualified pharmacists improves. This care consists of much more than just ensuring good medication use. The future will likely see these practices continue to develop.